Communicable Diseases Surveillance: CDI volume 24 issue 4 (2000) - No authors listed (Communicable Diseases Intelligence, 2000)
Communicable Diseases Surveillance: Highlights for March 2000 (bloodborne diseases, gastrointestinal diseases, quarantinable diseases, sexually transmissible diseases, vectorborne diseases, vaccine preventable diseases, other diseases, Echovirus 30 reports 1990-2000); National Notifiable Diseases Surveillance System tables, 28 February to 26 March 2000; Laboratory Serology and Virology Reporting Scheme tables, 1 to 31 March 2000; Australian Sentinel Practice Research Network report tables, 28 February to 26 March 2000; Rotavirus surveillance, reporting period June to December 1999; HIV and AIDS surveillance, reporting period 1 to 30 November 1999, assessed as at 29 February 2000; Australian childhood immunisation coverage, 1 October to 31 December 1999 cohort, assessed as at 31 March 2000.